2021
DOI: 10.1017/s0031182021001566
|View full text |Cite
|
Sign up to set email alerts
|

Molecular discrimination and genetic diversity of three common tick-borne pathogens in dogs in Thailand

Abstract: There was little information regarding the occurrence of canine vector-borne disease (CVBDs) in shelter dogs in Thailand. This work is the first report regarding a molecular method used to determine the occurrence and genetic diversity of three canine tick-borne pathogens (TBPs) (Hepatozoon canis, Anaplasma platys and Ehrlichia canis) in blood samples from 275 shelter dogs in the north and central areas of Thailand. The PCR results based on the 18S rRNA and 16S rRNA genes showed that 71 (25.82%) dogs were posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…A composite study in India reported that the overall prevalence rates of ehrlichiosis by microscopic examination, commercial dot-ELISA, and nested PCR assay were 1.3%, 19.1%, and 5.8%, respectively [21]. The rate determined by microscopic examination is similar to that reported for Thailand, although the occurrence of CME using the PCR test was higher than that in India [9][10][11][12][13]22]. The sensitivity of an E. canis test also depends on the stage of infection at the time of sampling.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…A composite study in India reported that the overall prevalence rates of ehrlichiosis by microscopic examination, commercial dot-ELISA, and nested PCR assay were 1.3%, 19.1%, and 5.8%, respectively [21]. The rate determined by microscopic examination is similar to that reported for Thailand, although the occurrence of CME using the PCR test was higher than that in India [9][10][11][12][13]22]. The sensitivity of an E. canis test also depends on the stage of infection at the time of sampling.…”
Section: Discussionsupporting
confidence: 55%
“…CME is widely distributed in tropical, Mediterranean, and subtropical climates, including Europe [1,2], the United States [3], Costa Rica [4], Brazil [5], and Asia [6][7][8]. In Thailand, the reported prevalence of E. canis identified using polymerase chain reaction (PCR) in all parts of the country ranges from 7.6% to 38.3% [9][10][11][12][13]. Transstadial transmission occurs in all tick stages, and infection can result while feeding on infected dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR reaction mixtures composed of 50 ng of DNA template, 0.2 mM of the respective primers, 200 mM of each deoxynucleoside triphosphate, standard Taq reaction buffer, and 1.25 U Taq DNA polymerase (BioLabs, USA) were prepared, and then, the PCR reactions were carried out in a thermal cycler (Bio-Rad, USA) under the conditions described by Poolsawat et al . [ 28 ]: 35 cycles of denaturation at 95°C for 45 s, annealing at 60°C and 63°C for the first and second steps of A. platys , annealing at 60°C and 53°C for the first and second steps of E. canis , annealing at 43°C of H. canis for 45 s, and extension at 72°C for 90 s followed by a final extension at 72°C for 5 min. The resultant PCR products were then identified with 1.2% agarose gels stained with FluoroStain™ DNA Fluorescent Staining Dye (Smobio, Taiwan) and observed under ultraviolet transilluminator.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of the CTBPs has not been well concluded in CTBD endemic areas, including Thailand, due to pathological characteristics, lack of affordable and sensitive diagnostics for CTBPs, and variable sample populations and locations across studies. Hence, subclinical CTBP infections in owned dogs are not well understood due to the scarcity of epidemiological studies [ 3 , 4 , 28 ]. Evaluation of the distribution of the CTBDs in healthy domestic dogs could support more effective risk assessment for the diseases and appropriate guidance on tick control for prevention.…”
Section: Introductionmentioning
confidence: 99%